2005
DOI: 10.1074/jbc.m414196200
|View full text |Cite
|
Sign up to set email alerts
|

Design and Construction of Highly Stable, Protease-resistant Chimeric Avidins

Abstract: The chicken avidin gene family consists of avidin and seven separate avidin-related genes (AVRs) 1-7. Avidin protein is a widely used biochemical tool, whereas the other family members have only recently been produced as recombinant proteins and characterized. In our previous study, AVR4 was found to be the most stable biotin binding protein thus far characterized (T m ‫؍‬ 106.4°C). In this study, we studied further the biotin-binding properties of AVR4. A decrease in the energy barrier between the biotin-boun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
58
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(64 citation statements)
references
References 39 publications
6
58
0
Order By: Relevance
“…Based on both sequence analysis and structural comparison the potential role of Tyr115 in AVR4 (equivalent to position 117 in avidin) in stabilizing the tetrameric structure was discussed previously ( Fig. 1; Hytönen et al, 2004bHytönen et al, , 2005. We have also found that I117Y stabilizes avidin .…”
Section: Structural Analysissupporting
confidence: 67%
“…Based on both sequence analysis and structural comparison the potential role of Tyr115 in AVR4 (equivalent to position 117 in avidin) in stabilizing the tetrameric structure was discussed previously ( Fig. 1; Hytönen et al, 2004bHytönen et al, , 2005. We have also found that I117Y stabilizes avidin .…”
Section: Structural Analysissupporting
confidence: 67%
“…A codon TGC encoding for C-terminal cysteine residue was added to the DNA sequence encoding for chimeric avidin equipped with ompA signal peptide from Bordetella avium [15,16] by PCR using Cys add 5 and Cys add 3 as primers (see support information). The resulting DNA amplicon was purified by agarose gel electrophoresis and isolated using the Illustra Gel purification kit (GE Healthcare).…”
Section: Preparation Of Cysteine-modified Chimeric Avidin (I117y129c)mentioning
confidence: 99%
“…To improve the stability of avidin immobilized on the polymer surfaces, a recently developed chimeric avidin could be used as an alternative to wt avidin. Genetically engineered chimeric avidin ChiAVD(I117Y) (hereinafter referred to as chimeric avidin) has improved thermostability and resistance against chemicals when compared with wt avidin or streptavidin [15,16]. The use of chimeric avidin for the immobilization enables the manufacture of sensor materials in which the stability and biotin-binding properties could be retained with excellent results over long storage periods or during demanding production stages.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, they can serve as a source of ideas when developing advanced (strept)avidin forms. The development of a non-glycosylated, acidic avidin mutant [104] and avidin-AVR chimeras [129] are examples of the latter. As described in previous sections, modification of (strept)avidin has until recently been limited to the homotetrameric approach.…”
Section: Conclusion -Views For Future Researchmentioning
confidence: 99%